2020
DOI: 10.3390/su12229464
|View full text |Cite
|
Sign up to set email alerts
|

Green Production as a Factor of Survival for Innovative Startups: Evidence from Italy

Abstract: Many studies have analyzed empirically the determinants of survival for innovative startup companies using data about the characteristics of entrepreneurs and management or focusing on firm- and industry-specific variables. However, no attempts have been made so far to assess the role of the environmental sustainability of the production process. Based on data describing the characteristics of the Italian innovative startups in the period 2009–2018, this article studies the differences in survival between gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
5
0
1
Order By: Relevance
“…Over the last three decades, this question has raised concerns about the sustainable survival of newly listed IPOs in capital markets across the globe [6]. It has been observed that newly launched IPOs face survival challenges initially, and their sustainable viability has remained a debatable issue [7,8]. The newly listed firms face the risk of long-term survival due to takeover threats, financial distress, and forced delisting by the regulatory authority [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three decades, this question has raised concerns about the sustainable survival of newly listed IPOs in capital markets across the globe [6]. It has been observed that newly launched IPOs face survival challenges initially, and their sustainable viability has remained a debatable issue [7,8]. The newly listed firms face the risk of long-term survival due to takeover threats, financial distress, and forced delisting by the regulatory authority [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…An exception to this trend is a study conducted by Serio (2020), which demonstrated that green innovative startups exhibit more than double the likelihood of survival compared to their non-green counterparts. This compelling evidence lends support to the notion that environmental sustainability can play a pivotal role in fostering economic development [12].…”
Section: The Role Of Startups In Sustainable Developmentmentioning
confidence: 52%
“…Finalmente, Serio et al (2020) analizaron las diferencias en la supervivencia entre start-ups que se enfocan en el medio ambiente y las que no, estableciendo que en la actualidad las start-ups innovadoras se han enfocado en solucionar problemas relacionados con el desarrollo sostenible y el impacto de las actividades del ser humano en el medio ambiente, concluyendo que aquellas que tienen procesos enfocados a la producción verde tienen mayor probabilidad de sobrevivir. En resumen, en esta categoría se identificaron diferentes relaciones entre la incubación de EBT y su relación con: empresa-universidad, parques científicos, emprendimiento universitario, formación de redes, oferta de servicios, creación de nuevas EBT, desempeño EBT, gobernanza, redes comerciales y talento humano.…”
Section: / 31unclassified